The Status of Assessments and Treatments for Osteoporosis in Patients 5 Years after Total Hip Arthroplasty: A Cross-Sectional Survey of 194 Post-THA Patients - Keiji Kamo; Hiroaki Kijima; Koichiro Okuyama; Shin Yamada; Natsuo Konishi; Hitoshi Kubota; Hiroshi Tazawa; Naohisa Miyakoshi; Yoichi Shimada (Advances in Orthopedics)
Background. Assessments for osteoporosis in patients who have undergone total hip arthroplasty (THA) are very important with respect to the clinical results. However, few studies have investigated the status of the assessments and treatments for osteoporosis in post-THA patients. The purpose of this multicenter study was to investigate the status of assessments and treatments for osteoporosis in post-THA patients. Methods. The results of a self-report questionnaire and the medical records of 194 post-THA patients over 40 years of age who visited the outpatient departments of the five hospitals participating in the study were analyzed. Results. A total of 125 patients (64.4%) had been examined for osteoporosis, and 69 patients (35.6%) had never been assessed for osteoporosis. It was assumed, based on the questionnaire results, that 50 (40%) of the 125 patients should have been receiving treatment for osteoporosis. Forty-five (90%) of these 50 patients were actually taking medication for osteoporosis at the time of the investigation. Overall, a total of 58 (29.9%) patients were receiving treatment for osteoporosis. Conclusions. The present survey revealed that 64.4% of post-THA patients had been evaluated for osteoporosis. Moreover, while 40% of post-THA patients over 40 years of age may require treatment for osteoporosis, only 29.9% were actually receiving treatment.